PENGARUH ROA DAN TVA TERHADAP ABNORMAL RETURN SAHAM PADA PERUSAHAAN-PERUSAHAAN TERDAFTAR DI BEI YANG MELAKUKAN STOCK SPLIT PADA TAHUN 2009-2013 - NELA SARI, DIAN (Jurnal Ilmu Manajemen (JIM), 2016)
BEI is a capital market that facilitate companies in finding investors by selling shares or distribute shares of the company. Stock growers will get a refund of planting stock (stock return) is, in the stock returns sometimes there are discrepancies between the actual return expectations with your return. It is called abnormal stock return. There are several things that affect abnormal stock returns, in this study the researchers chose a variabel return on assets (ROA) and tranding volume activity (TVA) as an independent variabel. Sampling of this study conducted by purposive sampling method. The number of companies that were sampled, there were 15 companies. The result showed that ROA no significant effect on abnormal stock return as a value greater that 0.05. On the test of t = 0.771 and Sig. = 0.456. While on TVA variables as ROA research result that do not significantly affect abnormal stock return to the test value t = 0.009 and Sig. = 0.0993. Keywords: abnormal stock return, ROA, TVA, BEI